Lateral Wear’s Effect on the Vehicle Dynamics Behavior with Out-of-round Wheel - DENG Yongguo (机车电传动)
In order to investigate the wheel treads’ lateral wear’s effect on the vehicle dynamics behavior with out-of-round wheel, secondary development for the existing SIMPACK software was done, and vehicle system dynamics model was established, considering the measured lateral wear of wheel treads. The results showed that: vehicle dynamics results response law was mainly affected by out-ofround wheel, while the wheel treads’ lateral wear largely contributed to the average of the results.